A32 THE REGULATION OF INTESTINAL SMOOTH MUSCLE CELL PROLIFERATION IN CROHN'S DISEASE – IS NR4A1 A NOVEL TARGET TO TREAT FIBROSTENOSIS?. (26th February 2020) - Szczepanski, H; Tsai, Y; Venu, V P; Alston, L; Hirota, S A
Abstract: Background: Intestinal fibrosis and stricture formation are common complications of Crohn's disease (CD). Recently, the stricturing phenotype has been recognized to be primarily attributable to hypertrophy/hyperplasia of smooth muscle, rather than an increase in fibrosis alone. Despite advances in treatment of CD, current therapies do little to prevent or reverse strictures. NR4A1 is an orphan nuclear receptor that has been reported as anti-fibrotic in non-intestinal systems and exhibits anti-proliferative effects in smooth muscle cells (SMCs). NR4A1 gene variants have been associated with increased risk of IBD, however, the mechanisms regulating NR4A1 expression and its role in intestinal SMC function has not been investigated. Aims: To characterize and understand the role of NR4A1 activation in the regulation of mitogen-induced proliferation of intestinal SMCs. Methods: Primary intestinal SMCs were isolated from Nr4a1 +/+ and Nr4a1 -/- mice. Furthermore, a commercially sourced human primary intestinal SMC line was used. To assess the response of SMCs to culture and identify growth differences, proliferation was measured via trypan blue exclusion and EdU incorporation. In mouse and human SMCs, proliferation was induced by platelet-derived growth factor-BB (PDGF-BB) and NR4A1 activation was assessed by pretreating with selective agonists, cytosporone B (Csn-B) and 6-mercaptopurine (6-MP), at various concentrations. Mass spectrometry was used to characterize proteomic differences between Nr4a1 +/+ and Nr4a1 -/- SMCs. Expression levels of NR4A1 were assessed by qPCR and western blot after mitogen exposure and Csn-B treatment. Results: Nr4a1 -/- cells exhibited a significantly higher rate of proliferation compared to Nr4a1 +/+ cells, under both basal and mitogen-exposed conditions. Proteomic analysis showed that Nr4a1 -/- SMCs exhibited increased expression of proteins related to the cell cycle and metabolism, compared to Nr4a1 +/+ SMCs. Pretreating human intestinal SMCs with Csn-B and 6-MP significantly attenuated proliferation induced by PDGF-BB. Similar effects were observed in Nr4a1 +/+ SMCs, however, the anti-proliferative effect of Csn-B was absent in Nr4a1 -/- cells. Furthermore, NR4A1 expression was rapidly induced by Csn-B and PDGF-BB, the latter response suggesting the existence of a potential negative feedback mechanism to control mitogen-induced SMC proliferation. Conclusions: Our results suggest that NR4A1 is a critical regulator of intestinal SMC proliferation and its induction by mitogens may contribute to a negative feedback loop to control smooth muscle growth. These data support targeting NR4A1 to treat excessive smooth muscle hypertrophy/hyperplasia that contributes to tissue remodelling observed in fibrostenotic CD. Funding Agencies: CAG, CCC, CIHR